2004
DOI: 10.3402/ijch.v63i0.17924
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiological and morphofunctional aspects of arterial hypertension under circumpolar conditions

Abstract: Introduction. Nowadays the problem of population health in the northern areas is of great importance. While evaluating human adaptation to the extreme geoecological northern conditions the state of the cardiovascular system can be used as an index of effective compensatory adaptation. Study design. The data on 24-hour BP monitoring, data of echocardiography and heliogeophysical factors in different periods of ontogenesis in 317 patients, living in the north of the Tyumen region, were analysed to estimate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The normal functioning of this system provides rate of blood circulation and consequently tissue metabolism, which are optimal for certain conditions. There are studies that consider the effect of heliogeophysical factors: solar activity and disturbances of the geomagnetic field during the study on the state of the cardio-vascular system [8][9][10][11][12][13]. The possibility of influence of heliogeophysical factors in early human ontogenesis on the risk of development of cardiovascular diseases was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The normal functioning of this system provides rate of blood circulation and consequently tissue metabolism, which are optimal for certain conditions. There are studies that consider the effect of heliogeophysical factors: solar activity and disturbances of the geomagnetic field during the study on the state of the cardio-vascular system [8][9][10][11][12][13]. The possibility of influence of heliogeophysical factors in early human ontogenesis on the risk of development of cardiovascular diseases was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that greater numbers of circumpolar residents in Russia have systemic hypertension than residents in other regions of the country (1)(2)(3). Diabetes mellitus increases the severity of symptoms caused by coronary artery disease (CAD) in patients with both diseases (4).…”
Section: Introductionmentioning
confidence: 99%